Current Advances in Sustained Release Microneedles - Guangsheng Du; Xun Sun (Georg Thieme Verlag KG, 2020)
Microneedles have been extensively investigated for intradermal delivery of drugs and vaccines due to advantages including high skin delivery efficiency, improved patient compliance, and potential for self-administration. However, traditional microneedles cannot regulate the release kinetics of payloads, limiting therapeutic utility of the biotherapeutics. Recently, several types of microneedles with sustained release properties, including slow-dissolving microneedles made of hydrophilic polymers, degradable microneedles made of hydrophobic polymers, and bioresponsive microneedles made of bioresponsive polymers, have been developed and investigated for intradermal delivery of the biotherapeutics, aiming for improving their therapeutic potency, reducing side effects and administration frequency, and further improving patient compliance. In this review, we introduced different types of microneedles that have been designed for sustained release of the payloads, summarized various applications of these microneedles, and discussed the future prospects of this technology.